Consequential-based life cycle assessment of reducing the concentrates supply level in the diet fed to lactating cows in the alpine dairy farming system - Marco Berton; Stefano Bovolenta; Luigi Gallo; Maurizio Ramanzin; Mirco Corazzin; Enrico Sturaro (Italian Journal of Animal Science, 2023)
This study aimed to assess the consequences of reducing the concentrates supply level (CSL) in the lactating cows’ diet on Alpine dairy system’s GHG emissions. Consequential-based Life Cycle Assessment (cLCA) was adopted to assess the consequences within the ‘dairy_system’ (farm plus milk processing) and outside (‘expanded_system’). The functional unit was 1 kg of protein and fat (ProtFat). Data (1-year average) originated from 40 dairy farms in the Alps, collected through farm questionnaires during farm visits. Emissions were evaluated without (GWP) and with land-based emissions (crop- (GWP_LULUC_cb) or global-based (GWP_LULUC_gb) method). The feed conversion ratio was computed in terms of potentially human-edible gross energy (HeECR, MJ feed/MJ milk). Three scenarios were explored: 100% (t0), 75% (t175), and 50% (t150) of the initial CSL. Impact values for both systems were analysed with a mixed model to test the effect of the scenarios. At ‘dairy_system’, 1 kg ProtFat caused 19.0 (GWP), 22.9 (GWP_LULUC_cb) and 23.4 kg CO2-eq (GWP_LULUC_gb) at t0 and HeECR resulted in 0.71 MJ feed/MJ milk. The CSL reduction from t0 to t175 and t150 significantly increased impact values (2–11%) and decreased HeECR (from −10 to −23%). Considering ‘expanded_system’, CSL reduction significantly increased GWP (4%) and GWP_LULUC_gb (3%) but decreased GWP_LULUC_cb (up to −4%). In conclusion, cLCA-based approach evidenced that CSL reductions implied diversified effects on GHG emissions, at Alpine dairy system and at food supply level, giving new insights into the challenge of reducing GHG emissions while favouring the decoupling of milk production from the use of human-edible resources.Highlights Consequential Life Cycle Assessment of reducing concentrates supply (CSL) to lactating cows on the GHG emission of Alpine dairy products was analysed GHGs per protein plus fat in the product increased with decreasing CSL (75% and 50% of initial CSL) but can decrease considering land-use change GHG Decoupling Alpine dairy production from concentrates could be environmentally challenging but feasible